Laboratory investigation of tyre sliding grip coefficient - Ivanov, Rosen; Rusev, Rusi; Ilchev, Plamen (Transport, 2006)
The paper presents the results of a laboratory investigation on the variation of the tyre sliding grip coefficient depending on the tyre construction, the air pressure, the vertical load and the wheel camber. Eight different models of tyres are tested. A significant reduction of the tyre sliding grip coefficient on a hard ground was registered, when the tyre pressure is low and the wheel camber is bigger. The analysis of results and explanation of causes are done.First Published Online: 27 Oct 2010